Tuning Hole and Electron Transfer from Photoexcited CdSe Quantum Dots to Phenol Derivatives: Effect of Electron‐Donating and ‐Withdrawing Moieties. Issue 30 (10th May 2017) - Debnath, Tushar; Sebastian, Deepa; Maiti, Sourav; Ghosh, Hirendra N.
Abstract: Charge‐transfer processes from photoexcited CdSe quantum dots (QDs) to phenol derivatives with electron‐ donating (4‐methoxy) and ‐withdrawing (4‐nitro) moieties have been demonstrated by using steady‐state and time‐ resolved emission and femtosecond transient absorption spectroscopy. Steady‐state and time‐resolved emission studies suggest that in the presence of both 4‐nitrophenol (4NP) and 4‐methoxyphenol (4MP) CdSe QDs luminescence is quenched. Stern–Volmer analysis suggests both static and dynamic mechanisms are active for both the QD/phenol composites. Cyclic voltammetric analysis recommends that photoexcited CdSe QDs can donate electrons to 4NP and holes to 4MP. To reconfirm both electron‐ and hole‐transfer mechanisms, CdSe/CdS quasi‐type II and CdSe/CdTe type II core–shell nanocrystals were synthesized and photoluminescence quenching was monitored in the absence and presence of both 4NP and 4MP, for which hole and electron transfer were systematically restricted. Results suggest that indeed electron and hole transfer take place from photoexcited CdSe to 4NP and 4MP, respectively. To monitor the charge‐transfer dynamics in both systems on an early timescale, femtosecond transient absorption spectroscopic techniques have been employed. Electron and hole transfer and charge‐recombination dynamics are discussed and the effect of electron‐donating and ‐withdrawing groups has been demonstrated. Abstract : A sense of direction : Electron‐withdrawing 4‐nitrophenol (4‐NP) act as an electron quencher, whereas electron‐donating 4‐methoxyphenol (4‐MP) acts as a hole quencher in CdSe nanocrystals (see figure). Thus, by varying the substituent in phenol, favorable energy‐level alignment results in changes to the quenching behavior.